Preliminary study on phosphate solubilizing Bacillus subtilis strain Q3 and Paenibacillus sp. strain Q6 for improving cotton growth under alkaline conditions - Maqshoof Ahmad; Iqra Ahmad; Thomas H. Hilger; Sajid M. Nadeem; Muhammad F. Akhtar; Moazzam Jamil; Azhar Hussain; Zahir A. Zahir (PeerJ, 2018)
Background Low phosphorus availability limits crop production in alkaline calcareous soils in semi-arid regions including Pakistan. Phosphate solubilizing bacteria may improve crop growth on alkaline calcareous soils due to their ability to enhance P availability. Methods Twenty rhizobacterial isolates (Q1–Q20) were isolated from rhizosphere of cotton and characterized for their growth promoting attributes in vitro. The selected phosphate solubilizing isolates were further screened for their ability to improve cotton growth under axenic conditions (jar trial). The phosphorus solubilization capacities of selected strains were quantified and these strains were identified through 16S rDNA sequencing. Results Isolates Q2, Q3, Q6, Q7, Q8, Q13 and Q14 were able to solubilize phosphate from insoluble sources. Most of these isolates also possessed other traits including catalase activity and ammonia production. The growth promotion assay showed that Q3 was significantly better than most of the other isolates followed by Q6. Maximum root colonization (4.34 × 106 cfu g−1) was observed in case of isolate Q6 followed by Q3. The phosphorus solubilization capacities of these strains were quantified, showing a maximum phosphorus solubilization by Q3 (optical density 2.605 ± 0.06) followed by the Q6 strain. The strain Q3 was identified as Bacillus subtilis (accession # KX788864) and Q6 as Paenibacillus sp. (accession # KX788865) through 16S rDNA sequencing. Discussion The bacterial isolates varied in their abilities for different growth promoting traits. The selected PGPR Bacillus subtilis strain Q3 and Paenibacillus sp. strain Q6 have multifarious growth promoting traits including ability to grow at higher EC and pH levels, and phosphorus solubilizing ability. These strains can efficiently colonize cotton roots under salt affected soils and help plants in phosphorus nutrition. It is concluded that both strains are potential candidates for promoting cotton growth under alkaline conditions, however further investigation is required to determine their potential for field application.